Learning Chemistry using Course Review Horay (CRH) Model Toward Students Learning Activity X Grade In SMA Negeri 1 Muntilan In Nomenclature Name Of Chemical Compounds Materials - Nimas Putri Dewi Puspitaningrum; Widinda Normalia Arlianty (Universitas Islam Indonesia, 2019)
The purpose of this study was to determine the difference of implementation the Course Review Horay (CRH) model on learning activities of students grade X SMA Negeri 1 Muntilan, academic year 2017/2018 in nomenclature of chemical compounds material. This research is an experimental research. Population of this study was all class X students of SMA Negeri 1 Muntilan on 2017/2018 school year, with a total of 7 classes. Samples were taken by purposive sampling technique consist of 2 classes. Data collection techniques used non-test methods. Form of assessment used are observation sheets. Data analysis techniques using the Mann Whitney-U test. Based on the results of the study it can be concluded: There was different of chemistry learning with the CRH model on student learning activities in Nomerclature of Chemical Compounds material.